If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(-7) + -5y = -6 Multiply 8 * -7 -56 + -5y = -6 Solving -56 + -5y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + -5y = -6 + 56 Combine like terms: -56 + 56 = 0 0 + -5y = -6 + 56 -5y = -6 + 56 Combine like terms: -6 + 56 = 50 -5y = 50 Divide each side by '-5'. y = -10 Simplifying y = -10
| 4(s+5)=28 | | 21=12+b | | Y=4x^2+8x-1 | | -3x-6=-30-x | | 11600/4 | | 6x+18=2x-32 | | W+1=2 | | (x+2)2+(y-12)2=36 | | 15x-10y=20 | | 2.5x^2-8*x=20 | | -6n+(-12)+4n= | | Log(x+2)+log(x-1)= | | 6+6r=12 | | 7/(x-8)=3/x | | 3x-8=-4x-92 | | 50x=80x | | 15=46-(2y+1) | | (4-1/3x)^3 | | 64-16y+2y^2=32 | | 4w+14=46 | | X^2+y^2+41=0 | | og(x+2)+log(x-1)=1 | | 3/5x1/5 | | 4x(3+8)-7= | | -7y-24=-8-9 | | 2x-(3-7x)+4(3-x)=7x-3(x-1) | | 4w-4x-y+3w+18x-8y= | | 2x+8=3-2x | | 1=9-3 | | T-(x-8)=-2 | | 18P-226=48 | | (x-4)(x^2+3)-(x-4)(6x-2)=0 |